Key Driver of Repurchase Intention in the Poultry Farming Input Market in Indonesia - S. P. Syahlani; F. T. Haryadi; A. A. Setyawan; I. Mayasari; N. M. A. K. Dewi; N. H. Qui (Tropical Animal Science Journal, 2022)
Regulatory changes increase the competitiveness of agribusiness input market, thus requiring input supply companies to improve service quality to maintain customer loyalty. This study aims to determine the role of customer comfort, salesperson expertise, and salesperson affection to influence customer satisfaction and delight and the effects on repurchase intention in poultry agribusiness context. Respondents were selected through judgmental sampling method who were the farmers who buy certain brand of poultry input for farm production process. Data were collected through survey using self-reported of questionnaire. The data obtained were tested for validity and reliability and examined by path analysis with Partial Least Square software. The results showed that customer comfort and customer affection influenced customer satisfaction and customer delight. However, salesperson expertise did not influence customer satisfaction and delight. Furthermore, repurchase intention in poultry farming input market was affected by customer satisfaction but not by customer delight. Therefore, it can be concluded that salesperson affection was found as the most important factor and followed by customer comfort to influence repurchase intention behavior through customer satisfaction.